Ulitization of Oil Palm Empty Bunches Waste as a Growth Media for Straw Mushrooms - Hastuti, Liana Dwi Sri; Munir, Erman; Tanjung, Rendra Syahputra; Ningrum, Iradani Yupita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Straw Mushroom (Volvariella volvaceae) as well asmushrooms edible otherhave been developed in Indonesia, including North Sumatra as a substitute for animal protein. Mushrooms or also known as button mushrooms are vegetables that are recognized to have high nutritional value, and are even believed to have medicinal properties for various types of diseases so that they have a fairly high selling value. Some studies report that in 100 grams of mushroom, only 0.17% fat is contained and even better, this fat is not bad fat. Seeing the high demand because of its nutritional value, and its rich content, its taste that is liked by many people, mushroom cultivation has a very promising market value. Basically until now the demand for mushroom continues to increase, but farmers have not been able to meet market needs. good quality start to be limited. Some farmers have started to switch to alternative planting media which is currently mostly practiced, namely oil palm pulp or empty palm oil bunches (TKKS). EFB is a waste that is very easy and is found mostly around palm oil processing factories, whose use has been limited so far as heating materials for boilers and particle wood, many empty bunches have not been utilized. This service aims to provide training in the form of mushroom cultivation using TKKS, as well as provide training in the form of post-harvest handling which is important given the lack of understanding of farmers in production and marketing activities.